Analisis Kinerja Keuangan Pemerintah Kabupaten/Kota Se-Propinsi Lampung - Herry Goenawan Soedarsa; Avrina Tryasmarini Dwi Putri (Universitas Bandar Lampung (UBL), 2014)
According to UU No. 17 / 2003 about state of financial claims that regional leaders should give the stewardship of the budget implementation in the form of financial report to parliament.Such financial statement covering a report the realization of regional, at least the balance, the report cash flow and the record on the financial statements.In accordance with the mandate pp no. 24 / 2005 about government, the accounting standard we need to be a assessment to the financial management of local governments in order to assess whether related regional governments managed to carry out his duty with good or not. The aim of this research is to find out if there are differences financial performance governments city se-propinsi lampung in 2011 and 2012 ' s independence, based on an indicator effectiveness, efficiency and growth of regional financial. Data used in this research is data skunder, in the form of a report the realization of budget district 2011-2012 originating from BPK-RI lampung area. he analysis used is an analysis of qualitative and quantitative analysis by the instrument in form of independent analysis of a sample t test with standard of significance 0.05 or 5 %.